2010
DOI: 10.1021/bi101057v
|View full text |Cite
|
Sign up to set email alerts
|

TAT Fusion Protein Transduction into Isolated Mitochondria Is Accelerated by Sodium Channel Inhibitors

Abstract: Stringent control of ion and protein transport across the mitochondrial membranes is required to maintain mitochondrial function and biogenesis. In particular, the inner mitochondrial membrane is generally impermeable to proteins entering the matrix except via tightly regulated protein import mechanisms. Recently, cell penetrant peptides have been shown to move across the inner mitochondrial membrane in a manner suggesting an independent mechanism. HIV-1 transactivator of transcription (TAT) is an arginine-ric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…Heart mitochondria were freshly isolated on the day of the experiments using the previously described methods (20). Briefly, hearts were homogenized in ice-cold mitochondrial isolation buffer (20 mM HEPES pH 7.4, 190 mM mannitol, and 70 mM sucrose) and then subjected to three rounds of differential centrifugation at 700 g, 900 g, and 1,000 g at 4°C for 10 min to remove cell debris and nuclei.…”
Section: Methodsmentioning
confidence: 99%
“…Heart mitochondria were freshly isolated on the day of the experiments using the previously described methods (20). Briefly, hearts were homogenized in ice-cold mitochondrial isolation buffer (20 mM HEPES pH 7.4, 190 mM mannitol, and 70 mM sucrose) and then subjected to three rounds of differential centrifugation at 700 g, 900 g, and 1,000 g at 4°C for 10 min to remove cell debris and nuclei.…”
Section: Methodsmentioning
confidence: 99%
“…PTDs, such as TAT, have the ability to penetrate the plasma membrane as well as the mitochondrial membranes (26,35,36), leading to the possible application of the PTD technology to a protein-therapeutic approach for mitochondrial disorders. Besides our research regarding the TAT-LAD fusion protein (see the Introduction), a number of studies have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…into pregnant mice, was detected in mitochondria of both maternal and fetal organs, like heart and brain. A novel mechanism for TAT transduction of mitochondrial membranes through the mitochondrial sodium channels has been proposed (173), different from the endocytotic mechanisms proposed for TAT transduction of plasma membranes.…”
Section: Ptd-mediated Protein Replacement Therapy (Prt) As a Therapeumentioning
confidence: 95%
“…The ability of PTDs (like TAT) to penetrate not only the plasma membrane but also the mitochondrial membranes (154,172,173) "opened the door" for the application of PTD technology as a putative protein therapeutic approach of mitochondrial disorders. In general, TAT could mediate transduction of the PT either from its N-terminal (TAT-X fusion protein) or its C-terminal (X-TAT fusion protein).…”
Section: Ptd-mediated Protein Replacement Therapy (Prt) As a Therapeumentioning
confidence: 99%